Daratumumab (DARA) Plus Carfilzomib, Pomalidomide, Dexamethasone (KPd) in Lenalidomide Refractory Multiple Myeloma (MM): A Multi-Center MMRC Study - Jasielec, Jagoda; Zonder, Jeff; Derman, Benjamin A; Reece, Donna E.; Cole, Craig E.; Berdeja, Jesus G.; Wolfe, Brittany; Major, Sarah; Tinari, Kathryn M.; Stefka, Andrew; Fazzi, Fabrizio; Whelan, Megan; et al. (Blood, 2020)
Introduction: Lenalidomide (LEN) is a cornerstone in the treatment of newly diagnosed MM both as part of induction and maintenance therapy. As a result, most patients at first or second relapse are LEN exposed/refractory creating a need for effective 2nd line and salvage therapies. While no standard of care regimen has been established in early relapse, several therapies have been evaluated combining second generation immunomodulatory agents, proteasome inhibitors, and daratumumab. We have previously reported the results from the phase I/II trial of KPd demonstrating excellent efficacy in a LEN-refractory patient population. Here, we present the first efficacy and safety results from the cohort in which DARA was added to KPd (D-KPd). Methods: This is a multi-center, open-label, Phase 1b/2 study in subjects with relapsed MM with two sequential treatment cohorts: KPd and D-KPd. Eligibility criteria and KPd doses and schedules were identical for both cohorts. Subjects with measurable disease that progressed after at least 1 prior therapy (LEN refractory disease was required for 2nd-line therapy and LEN refractory/exposed for ≥ 3rd line) were eligible. The KPd cohort has completed enrollment (n=67) and results have been previously reported. The D-KPd cohort received treatment on the following 28-day schedule: Pomalidomide 4 mg daily on days 1-21 for cycles 1-8+, Carfilzomib 20/27 mg/m2 on days 1,2,8,9,15,16 for C1-8, then 1,2,15,16 for C9+ (maintenance), dexamethasone 20 mg days 1,2,8,9,15,16,22,23 for C1-2, then 40 mg days 1,8,15,22 for C3+. DARA was administered as per standard schedule, weekly for the first 2 cycles, then every 2 weeks for cycles 3-6, and monthly thereafter. A Minimax two-stage design was employed for enrollment of subjects on this cohort. Twenty-one patients were required to accrue to the first stage, with at least 4 responders of ≥nCR at 4 cycles necessary to accrue to second stage for a total of 34 pts. Primary endpoint was rate of nCR/CR as per IMWG criteria. Minimal residual disease (MRD) was evaluated by 10-color flow cytometry with limit of detection (LOD) 10-4-10-5 and will also be assessed by next-generation sequencing (LOD 10-5-10-6). Secondary endpoints include overall response rate, depth of response, progression-free survival (PFS), and overall survival. Per study design, a nCR/CR rate of >35% (over the historical 20% rate) would support further study of the D-KPd regimen. Results: As of July 29, 2020, all 22 subjects who were enrolled into the D-KPd cohort were evaluable for safety and the primary endpoint. Median age was 62 (range 37-74) with a median of 1 (range 1-3) prior lines of therapy. 81% of patients were LEN refractory, and high-risk cytogenetics per IMWG criteria were present in 12/19 (68%) evaluable patients. Subjects completed a median of 12.5 cycles (range 2-33) of therapy and 21 (95%) subjects completed at least 4 cycles; 1 subject progressed after cycle 2. In the ITT population (n=22), after 4 cycles, 86% achieved ≥PR and 46% ≥nCR, warranting further enrollment to a second stage. At best response, the ≥PR was 86% with 55% ≥nCR/CR, 45% ≥sCR, and 55% MRD negativity by flow cytometry (n=22). The most common grade 3-4 hematologic adverse events included neutropenia (64%), lymphopenia (36%), and febrile neutropenia (18%). The most common grade 3-4 non-hematologic adverse events included fatigue (27%), respiratory infections (23%), diarrhea (14%), and insomnia (14%). There was one thrombotic event (4.5%) which was grade 2. In comparison to the KPd cohort (67 patients with similar baseline characteristics), there was an improvement in efficacy as demonstrated by an increase in rate of ≥nCR at the end of 4 cycles (from 7% to 46%), as well as the best response (from 20% to 55%). High risk cytogenetics did not significantly affect response (≥nCR 46% at best response [all sCR]). With 20 months of follow-up, median PFS was not reached in the D-KPd cohort and 12-month PFS is 84% vs 63% for KPd. Rates of grade 3/4 cytopenias were higher in the D-KPd cohort. There was no treatment related mortality and 19 of 22 pts are alive. Conclusion: D-KPd demonstrates high efficacy in a population of patients with relapsed/refractory multiple myeloma enriched for high risk cytogenetics. MRD negativity by flow cytometry was achieved in 55% of subjects. The ≥nCR rate of 55% with D-KPd compares favorably to the 20% rate with KPd alone; based on the study design, this warrants further evaluation of D-KPd. Zonder:BMS, Celgene: Research Funding; Intellia, Amgen, Takeda, Janssen, Regeneron, Alnylam, Caelum, Oncopeptides: Consultancy. Reece:Janssen, Bristol-Myers Squibb, Amgen, Takeda: Consultancy, Honoraria; Janssen, Bristol-Myers Squibb: Membership on an entity's Board of Directors or advisory committees; Merck: Honoraria, Research Funding; Otsuka: Research Funding. Berdeja:Kesios: Research Funding; Karyopharm: Consultancy; Acetylon: Research Funding; Vivolux: Research Funding; Abbvie: Research Funding; Amgen: Consultancy, Research Funding; Bioclinica: Consultancy; BMS: Consultancy, Research Funding; Celgene: Consultancy, Research Funding; Cellularity: Research Funding; Constellation: Research Funding; CURIS: Research Funding; EMD Sorono: Research Funding; Genentech, Inc.: Research Funding; Glenmark: Research Funding; Janssen: Consultancy, Research Funding; Kite Pharma: Consultancy; Legend: Consultancy; Lilly: Research Funding; Novartis: Research Funding; Poseida: Research Funding; Takeda: Consultancy, Research Funding; Teva: Research Funding; Prothena: Consultancy; Servier: Consultancy; Bluebird: Research Funding; CRISPR Therapeutics: Consultancy, Research Funding. Jakubowiak:Adaptive, Juno: Consultancy, Honoraria; AbbVie, Amgen, BMS/Celgene, GSK, Janssen, Karyopharm: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees.